MANAJEMEN PERSEDIAAN BAHAN BAKU BAWANG PUTIH GORENG PADA UKM SOFIE LOCALFOOD DI KOTA PALU - Susi Agus Stevani; Dance Dance; Husnul khatima (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
Garlic Sofie Localfood is one of the businesses engaged in agro-industry that utilizes garlic as the main raw material. Sofie Localfood's fried garlic products still have difficulty in regulating the production process, due to delays in ordering raw materials, so SMEs buy raw materials elsewhere and require more costs and sometimes the raw materials are not as expected. Raw materials are one of the most important production factors because they support the smooth running of the production process. This study aims to find out how much economic raw material purchases (EOQ) for the supply of raw materials to SMEs Sofie Localfood, to find out how much safety stock (Safety Stock) to SMEs Sofie Localfood, to find out when is the right time for SMEs Sofie Localfood to do reordering (ROP) of raw material inventory, and to find out the total inventory cost (TIC) of raw materials at UKM Sofie Localfood, This research was conducted at UKM Sofie Localfood on Jalan Zebra IV, Lorong 1 No. 5 Palu City. The selection of this location was done purposively, with the consideration that Sofie Localfood is one of the businesses that produces garlic as the main raw material for making tempeh in Palu City. This research was conducted from April to June 2021. Respondents are owners and employees of UKM Sofie Localfood who were selected as sources of information in the study, the total number of respondents is 3 people. Based on data to be obtained from Sofie Localfood's business regarding raw material inventory management issues tempe, the data analysis used is Economic Order Quantity (EOQ), Safety Stock (Safety Stock), reorder (ROP) and total inventory cost (TIC). The results of this study indicate that the management of raw material inventory at SMEs Sofie localfood using the (Economic Order Quantity) method in JanuaryDecember 2020 an average of 31.17 kg/month. Safety stock (Safety Stock) of raw materials that is always available at UKM Sofie Localfood is 14.92 kg/month. The reorder point (reorder point) that SMEs Sofie Localfood must make in April-June 2021 is an average of 77.26 kg/month. The total cost of raw material inventory for garlic in the UKM Sofie Localfood is an average of Rp.58.157.86/month.